Fungicide free management of papaya Anthracnose (Colletotrichum gloeosporioides Penz.) disease using combined bio-rationales and bee wax in Organic Agriculture - Niveka, S.; Mikunthan, G.; Pakeerathan, K. (1st International Electronic Conference on Plant Science, 1–15 December 2020, 2020)
Papaya (Carica papaya L.) is an economical important orchard crop mainly cultivated in tropical and sub-tropical countries. Due its excellent medicinal value, papaw is recommended to consume daily by medical professionals as fresh fruit. Papaya production is highly being hampered by Papaya Anthracnose disease caused by Colletotrichum gloeosporioides which is inflicting major economic loss of around 40-100% while cultivation in field, transportation and storage in organic agriculture. An investigation was planned to assess the antifungal capacity of the medicinal plants Spinacia oleracea, Limonia acidissima, Allium sativum, Achyranthes aspera, Calotropis gigantea, Ocimum basilicum, Mukia scabrella, Ficus racemosa, Azadiracta indica, Ocimum tenuiflorum, Lantana camara and Ocimum cinnamonthat, combined with bee wax coating against papaya anthracnose disease. Fifty percent concentrations of botanical were extracted from dried leaves using methanol based solvent extraction method. Two sets of partially ripened non-infected marketable papaya fruits were collected and treated with 50% concentration of botanical extracts and allowed to dry. One set was coated with melted wax by spraying under cool conditions using power sprayer along with non-treated control. These experimental setups were arranged in a complete randomized design with five replicates. Four hours after wax coating, both sets were inoculated with spores of C. gloeosporioides. Data on disease incidence, disease severity (0-5 scale), number of days for disease free period, pH, TSS were measured in both sets and ANOVA was performed using SAS software. Duncan’s Multiple Ranges Test (DMRT) was used to determine the least significant differences among the treatments at P <0.05. Results show that disease incidence and severity in Ocimum basilicum + bee wax treated fruits was 0% and 5%, respectively and significant at P <0.05 until 10th day of post-inoculation, thereafter, disease incidence and severity were increased slowly to 15% at 14th day of post-inoculation, but in other treatments and control, disease incidence and severity were varied from 60-80% and 100%, respectively, from 5th day of post-inoculation. Moreover, bee wax-coated papaya fruits showed significantly higher preserved days of maximum 17.047±3.86. Weight loss percentage, pH and TSS were not significantly on par among wax-coated treatments but were significant when compared with wax-free treatments. This study concludes that the combined application Ocimum basilicum + bee wax is a promising alternative to nasty fungicides.
Keywords: Papaya; Bio- ratinals; wax; Ocimum basilicum; Ocimum tenuiflorum